What is International Transport Law in the System of International Law? - Alexander G. Bogaturev; Yury N. Maleev (Московский журнал международного права, 2016)
There are some groups of norms in International Law, which have no general opinion on their nature. Exactly-whether they may be named as the branches of International Law. International Transport Law (ITL) is among them. The authors of the present article systematized corresponding criterions on the examples of some "of no doubt" brunches of International Law and supposed that the reader will decide himself in what degree these criterions may be used to the ITL and, correspondingly, whether it may be qualified as the brunch of International law.